Failure to perceive increased risk of fracture in women 55 years and older: the Global Longitudinal Study of Osteoporosis in Women (GLOW). - Siris, E; Gehlbach, S; Adachi, J; Boonen, S; Chapurlat, R; Compston, J; Cooper, C; Delmas, P; Díez-Pérez, A; Hooven, F; Lacroix, A; Netelenbos, J; et al. (2011)
UNLABELLED: We compared self-perception of fracture risk with actual risk among 60,393 postmenopausal women aged ≥55 years, using data from the Global Longitudinal Study of Osteoporosis in Women (GLOW). Most postmenopausal women with risk factors failed to appreciate their actual risk for fracture. Improved education about osteoporosis risk factors is needed. INTRODUCTION: This study seeks to compare self-perception of fracture risk with actual risk among postmenopausal women using data from GLOW. METHODS: GLOW is an international, observational, cohort study involving 723 physician practices in 17 sites in ten countries in Europe, North America, and Australia. Participants included 60,393 women ≥55 years attended by their physician during the previous 24 months. The sample was enriched so that two thirds were ≥65 years. Baseline surveys were mailed October 2006 to February 2008. Main outcome measures were self-perception of fracture risk in women with elevated risk vs women of the same age and frequency of risk factors for fragility fracture. RESULTS: In the overall study population, 19% (10,951/58,434) of women rated their risk of fracture as a little/much higher than that of women of the same age; 46% (27,138/58,434) said it was similar; 35% (20,345/58,434) believed it to be a little/much lower. Among women whose actual risk was increased based on the presence of any one of seven risk factors for fracture, the proportion who recognized their increased risk ranged from 19% for smokers to 39% for current users of glucocorticoid medication. Only 33% (4,185/12,612) of those with ≥2 risk factors perceived themselves as being at higher risk. Among women reporting a diagnosis of osteopenia or osteoporosis, only 25% and 43%, respectively, thought their risk was increased. CONCLUSION: In this international, observational study, most postmenopausal women with risk factors failed to appreciate their actual risk for fracture.